Originally Posted by

**ecMathGeek** Be careful with your signs and you should have no problems:

4x + 12 - 5x - 25 = -6x^2 - 48x - 90

First (always) combine like terms:

-x - 13 = -6x^2 - 48x - 90

Now move terms.

If we move the terms to the right, we get

-6x^2 - 48x + x - 90 + 13 = 0

-6x^2 - 47x - 77 = 0 ... multiply everything by -1

6x^2 + 47x + 77 = 0

If we move the terms to the left, we get

6x^2 - x + 48x - 13 + 90 = 0

6x^2 + 47x + 77 = 0

Notice that the two answers became the same (if I multiply one version by -1, that is).